2022
DOI: 10.1186/s13195-022-01041-4
|View full text |Cite
|
Sign up to set email alerts
|

A multiscale brain network model links Alzheimer’s disease-mediated neuronal hyperactivity to large-scale oscillatory slowing

Abstract: Background Neuronal hyperexcitability and inhibitory interneuron dysfunction are frequently observed in preclinical animal models of Alzheimer’s disease (AD). This study investigates whether these microscale abnormalities explain characteristic large-scale magnetoencephalography (MEG) activity in human early-stage AD patients. Methods To simulate spontaneous electrophysiological activity, we used a whole-brain computational network model comprised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(79 citation statements)
references
References 104 publications
3
76
0
Order By: Relevance
“…It has also been demonstrated that changes to theta oscillatory power – similar to what we observed herein – can be used to distinguish between prodromal AD and non-AD cases with cognitive decline [91]. The fact that our effects on oscillations agree with clinical human electrophysiological studies gives confidence that this is a method that could, in the future, be clinically useful as in compliment to EEG testing.…”
Section: Discussionsupporting
confidence: 78%
“…It has also been demonstrated that changes to theta oscillatory power – similar to what we observed herein – can be used to distinguish between prodromal AD and non-AD cases with cognitive decline [91]. The fact that our effects on oscillations agree with clinical human electrophysiological studies gives confidence that this is a method that could, in the future, be clinically useful as in compliment to EEG testing.…”
Section: Discussionsupporting
confidence: 78%
“…Previous models in AD research have lumped neural populations at each brain region into neural masses (neural mass models) (Ranasinghe et al 2022; Monteverdi et al 2022; van Nifterick et al 2022; Stefanovski et al 2021; Stefanovski et al 2019; Zimmermann et al 2018; de Haan et al 2017). Using neural mass models, recent studies have found a relationship between abnormal excitatory and inhibitory time-constants and spatial depositions of Aβ and tau (Ranasinghe et al 2022; Stefanovski et al 2019), have linked neuronal hyperactivity in preclinical AD to oscillatory slowing (van Nifterick et al 2022; Stefanovski et al 2019) and have developed a successful strategy to preserve network integrity during AD progression (de Haan et al 2017). A recent work has also used neural mass models to extract information about the excitatory/inhibitory balance in single subjects and suggested that AD subjects were characterized by increased global coupling and increased inhibition (Monteverdi et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…We obtained subject-specific relative contributions of the considered pathophysiological factors on neuronal activity and reconstructed proxy quantities for electro-(magneto-)encephalographic (E/MEG) sources in each brain region. Subsequently, we aimed to test the proposed pathophysiological - activity generator’s ability to validate reported spectral changes in AD, i.e., increases of theta band power (4–8 Hz) and decreases of power in the lower alpha band (alpha1, 8–10 Hz) 911 . Among the quantities contributing to the E/MEG model output, we also closely studied excitatory firings and changes to their magnitude given the influence of the toxic protein depositions (for definitions and further details on the calculations, see Methods, Integrative neuronal activity simulator ).…”
Section: Resultsmentioning
confidence: 99%
“…These disease processes also manifest differently given subject-specific genetic and environmental conditions 1, 8 . Models of multiple pathological markers and physiology can help reveal the connection between individual AD fingerprints and cognitive deficits 3, 9,10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation